Strategi Meningkatkan Mutu Produk untuk Memasuki Pasar Internasional (Studi pada Batik Tulis Klasik Kampung Giriloyo, Imogiri, Bantul) - Aftoni Sutanto (Forum Manajemen Indonesia (FMI), 2016)
The purpose of this study to formulate international business strategies classical batik in Kampung Giriloyo, Imogiri to enter the international market. Methods This study used a qualitative approach with descriptive research. Selection of informants is the snowball method approach. In connection with the problems faced by classical batik artisans to improve the quality of products and markets its products in the international market, there are several strategies to overcome them. Improving product quality through the process of writing to the storage batik cloth batik perfect. Development of classical batik not only by producers but also must be supported by all stakeholders. Support is expected to come from the relevant agencies with policies to encourage the development of classical batik artisans. Support e-commerce facilitation of college related to the development of the international business strategy for a classical batik artisans acceleration phase transformation of traditional batik artisans towards modernization phase of the business. Keywords: Batik classic, international markets, Giriloyo